2016
DOI: 10.1002/asia.201501204
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Properties of Rocket Propellants Evaluated through the Computational Determination of Heats of Formation of Nitrogen‐Rich Compounds

Abstract: The use of ab initio and DFT methods to calculate the enthalpies of formation of solid ionic compounds is described. The results obtained from the calculations are then compared with those from experimental measurements on nitrogen-rich salts of the 2,2-dimethyltriazanium cation (DMTZ) synthesized in our laboratory and on other nitrogen-rich ionic compounds. The importance of calculating accurate volumes and lattice enthalpies for the determination of heats of formation is also discussed. Furthermore, the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 113 publications
(213 reference statements)
0
12
0
Order By: Relevance
“…Previous studies on HOF quantum calculations were reported on related polynitrogenated compounds using various levels of theory. [16,17] The resulting calculated HOF values were compared with experimental ones, to select the most appropriate and accurate level of theory for such compounds. According to these results, compound method CBS-QB3 is the most accurate.…”
Section: Gas Phase Heat Of Formationmentioning
confidence: 99%
“…Previous studies on HOF quantum calculations were reported on related polynitrogenated compounds using various levels of theory. [16,17] The resulting calculated HOF values were compared with experimental ones, to select the most appropriate and accurate level of theory for such compounds. According to these results, compound method CBS-QB3 is the most accurate.…”
Section: Gas Phase Heat Of Formationmentioning
confidence: 99%
“…[33], Forquet et al. [28] demonstrated the effectiveness of using the CBS‐QB3 method. The last compound method used in this study is the G4 method [34].…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The volume of ions was obtained from an isodensity surface polarized continuum model (IPCM) calculation at the DFT B3LYP/6‐31G(d,p) level, similar method as Forquet et al. [28]. Corrections proposed by Rice et al.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Moreover, different oxidizing groups, e. g. nitro, nitrate, or nitramine groups, can be added to the HNC skeletons in order to increase the released energy [18]. HNC materials have been introduced as new candidates in different military applications, e. g. high explosives [19], rocket propellants [19][20], gun propellants [21], and pyrotechnic ingredients [19,22]. HNC materi-als are impressive candidates for new high energy density materials (HEDMs) because they have high densities, high enthalpies of formation, and favorable oxygen balances.…”
Section: Introductionmentioning
confidence: 99%